A role for a Rab4-like GTPase in endocytosis and in regulation of contractile vacuole structure and function in Dictyostelium discoideum. - Bush, J (1996)
The small Mr Rab4-like GTPase, RabD, localizes to the endosomal pathway and the contractile vacuole membrane system in Dictyostelium discoideum. Stably transformed cell lines overexpressing a dominant negative functioning RabD internalized fluid phase marker at 50% of the rate of wild-type cells. Mutant cells were also slower at recycling internalized fluid. Microscopic and biochemical approaches indicated that the transport of fluid to large postlysosome vacuoles was delayed in mutant cells, resulting in an accumulation in acidic smaller vesicles, probably lysosomes. Also, RabD N121I-expressing cell lines missorted a small but significant percentage of newly synthesized lysosomal alpha-mannosidase precursor polypeptides. However, the majority of the newly synthesized alpha-mannosidase was transported with normal kinetics and correctly delivered to lysosomes. Subcellular fractionation and immunofluorescent microscopy indicated that in mutant cells contractile vacuole membrane proteins were associated with compartments morphologically distinct from the normal reticular network. Osmotic tests revealed that the contractile vacuole functioned inefficiently in mutant cells. Our results suggest that RabD regulates membrane traffic along the endosomal pathway, and that this GTPase may play a role in regulating the structure and function of the contractile vacuole system by facilitating communication with the endosomal pathway.